THE SOCIODEMOGRAPHICS INFLUENCE IN THE KNOWLEDGE, PERCEPTION, AND BEHAVIOR OF OSTEOPOROSIS IN MALANG: A COMMUNITY-BASED STUDY: Pengaruh Sosiodemografi dengan Tingkat Pengetahuan, Persepsi, dan Perilaku tentang Osteoporosis di Malang: Studi Komunitas - Pratama, Mirza Zaka; Suryana, Bagus Putu Putra; Putra, Domy Pradana; Rahmad, Rahmad; Abellia, Gaby (Universitas Airlangga, 2024)
Background: Osteoporosis is a major global health issue that results in disability and high medical expenses. It can significantly impact both individuals and their caregivers, leading to pain, limitations in daily activities, and emotional distress. Purpose: This study observed the association of sociodemographic factors in affecting knowledge, perception, and behavior related to osteoporosis in a rural area of Malang, Indonesia. Methods: A cross-sectional study was conducted in a rural area of Malang to assess the knowledge, perception, and behavior of adults (â‰¥18 years old) toward osteoporosis. Participants were asked to fill in a validated questionnaire, which was selected randomly using a multistage stratified sampling technique. Collected data were analyzed on SPSS for Windows version 25.0. Results: The study included 376 randomly selected participants from various rural areas in Malang. The subjects mostly were within the 51-60 age group (34.0%), with female respondents accounting for 73.4% of the sample. On average, participants scored 1.8 (±2.5) for knowledge, 12.0 (±2.1) for perception, and 12.2 (±2.9) for behavior regarding osteoporosis. Both age and education levels showed associations with knowledge and perception, while only age was significantly linked to behavior concerning osteoporosis. Conclusions: Our study revealed a strong association between low educational levels, especially among the elderly, and the lack of knowledge, perceptions, and behavior toward osteoporosis.